A Review of the Causes of Pending Inpatient Claims to BPJS Kesehatan (Indonesia's National Health Insurance Agency) Using The 7m Framework at Ajibarang Regional Public Hospital - Fauzan Adi Fathurrahman; Cindy Rozza Bella (Proceedings Series on Health & Medical Sciences, 2026)
BPJS Kesehatan (Indonesia's National Health Insurance Agency) claims refer to the process of submitting health service costs to BPJS Kesehatan, which requires complete administrative, medical, and coding documentation. Pending claims occur due to discrepancies or incomplete documents, causing delays in payments and hospital cash flow. This study aims to identify the factors causing pending inpatient claims at Ajibarang Regional Public Hospital based on the elements of Man, Money, Material, Machine, Method, Motivation, and Media. Using a qualitative descriptive method with a case study approach, data was collected through in-depth interviews with the Head of the Medical Records Unit, internal verifiers, and coding officers, as well as a documentation study of pending claims in 2024. Data analysis applied the interactive model of Miles and Huberman, which involves data reduction, presentation, and conclusion drawing. Results revealed that out of 17,892 inpatient claims in 2024, 2,109 claims (11.79%) were pending. The primary cause was coding issues (54%), followed by administrative issues (29%) and medical issues (17.1%). Dominant factors included inaccurate diagnosis coding, incomplete documentation, differences in perception between physicians and BPJS verifiers, and technical system barriers. In conclusion, the causes of pending inpatient claims were mainly related to coding issues, followed by administrative and medical problems. Enhancements can be made through improved staff accuracy, coordination, and optimized information systems for smoother claim processing.